Insights into enhanced visible-light photocatalytic activity of CeO2 doped with nonmetal impurity from the first principles. (January 2016) - Yang, Ke; Huang, Wei-Qing; Xu, Liang; Luo, Kai-Wu; Yang, Yin-Cai; Huang, Gui-Fang
Abstract: The doped cerium dioxide (CeO2 ) nanomaterials have attracted intensive attention due to its enhanced photocatalytic activity in the visible light region, but still lacking is the theoretical understanding on the mechanism of this behavior. Herein, the origin of enhanced photocatalytic performance of doped CeO2 is systematically explored by using the first-principles calculation. The systematic study includes the effects of nonmetal C+N codoping on the electronic structure and optical proprties of CeO2 in comparison to the effect of individual dopants. The monodoping (B, C) introduces impurity states in the middle of gap. For the N–CeO2, the impurity levels are near the top of valence band at lower N concentration, while those are separated by more than 1.0 eV in the gap at higher N concentration. Interestingly, C+N codoping shifts up the Fermi level to the bottom of conduction band, and introduces impurity level close to the Fermi level. Moreover, the feasibility of the introduction of N into the CeO2 crystal structure is found to be enhanced in the presence of C. The reduced band gap and strong absorption induced by impurity levels are responsible for the enhanced photocatalytic activity of doped CeO2 in the visible region. These findings can rationalize the available experimental results and pave the way for developing CeO2 -based photocatalysts.